References to sex and gender differences in the social sciences: analysis of journal publication records (1971–2021) - Jakubowska, Honorata; Cichocki, Piotr; Jabkowski, Piotr (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
Based on the publication records of journal articles indexed in the Web of Science Social Sciences Citation Index, our analysis examines the underlying factors influencing the usage of ‘sex differences’ over ‘gender differences’ in Titles and Author Keywords. Our search query identified 16,362 articles published in 1971–2021 that use either of the phrases and have at least one of their Research Areas belonging to the Social Sciences. In concurrence with earlier research, we find a substantial shift towards using ‘gender’ in the 1980s. However, for records published after 1992, the Publication Year has a negligible aggregate impact on the likelihood of ‘gender’ over ‘sex’, although meaningful trend differences occur across subsets defined by article-level disciplinary associations. Using the available publication meta-data (Publication Year, Research Area, Publication Journal) as well as the results of topic modelling (LDA) on Titles and Abstracts, we implement multi-level regression modelling to demonstrate that the likelihood of referring to ‘gender’ rather than ‘sex’ is strongly influenced by article-level disciplinary associations and their topical classification. We find that Psychology articles, by far the most numerous, exhibit a lower propensity to use ‘gender’ than all the other Social Sciences, especially when collaborating with Life Sciences & Biomedicine.